Work-family Conflict Moderates the Impact of Childbearing on Subjective Well-Being - Vignoli, D; Matysiak, A; Mencarini, L (My University, 2015)
Many empirical studies find parents to be less happy than non-parents and parenthood to exert a negative effect on subjective well-being (SWB). We add to these findings by arguing that there is a key moderating factor that has been overlooked in previous research, the work-family conflict. In this paper we assesses the effect of parenthood on individuals’ SWB, taking into account that the birth of a child means an increase in work-family tensions, which may be substantial for some parents and relatively weak for others. To this end, we estimate fixed-effects models using panel data from the Household, Income and Labor Dynamics in Australia (HILDA) survey. We find that childbearing negatively affects SWB only when parents, and mothers, in particular, have to face a heavy work-family conflict.
SWELLFER working paper
Collegio Carlo Alberto Working Papers
Keywords: Health -- Wellbeing; Families -- Fertility; Employment -- Work/life Balance; Families and relationships; Health and wellbeing; Labour market; Employment; Health; Families; Work/life Balance; Fertility; Wellbeing; Families and relationships; Employment and unemployment; Health and wellbeing